2015
DOI: 10.1186/s13024-015-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Munc18-1 long splice variant in GABAergic terminals is associated with cognitive decline and increased risk of dementia in a community sample

Abstract: BackgroundPresynaptic terminals contribute to cognitive reserve, balancing the effects of age-related pathologies on cognitive function in the elderly. The presynaptic protein Munc18-1, alternatively spliced into long (M18L) or short (M18S) isoforms, is a critical modulator of neurotransmission. While subtle alterations in Munc18-1 have been shown to cause severe neuropsychiatric disorders with cognitive impairment, little information is known regarding the specific roles of Munc18-1 splice variants. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Co-immunoprecipitation (IP) and Western blotting (WB) were used in characterization experiments as described elsewhere [36]. Subcellular extractions yielding proteins enriched in (1) nuclear- (along with cell debris), (2) cysosolic-, (3) membrane-, (4) synaptosomal- and (5) myelin-associated compartments were performed as reported [18, 36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-immunoprecipitation (IP) and Western blotting (WB) were used in characterization experiments as described elsewhere [36]. Subcellular extractions yielding proteins enriched in (1) nuclear- (along with cell debris), (2) cysosolic-, (3) membrane-, (4) synaptosomal- and (5) myelin-associated compartments were performed as reported [18, 36].…”
Section: Methodsmentioning
confidence: 99%
“…Subcellular extractions yielding proteins enriched in (1) nuclear- (along with cell debris), (2) cysosolic-, (3) membrane-, (4) synaptosomal- and (5) myelin-associated compartments were performed as reported [18, 36]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a correlation was observed between the numbers of these interneurons and the apoptotic marker caspase-3 [ 226 ]. In another recent study, it was found that a long variant of the Munc18-1 protein (M18L) is important for presynaptic GABA function, and that expression of this protein is reduced in the AD frontal cortex [ 227 ]. The extent of this loss seemed to be correlated with greater cognitive decline and more severe AD pathology, and a statistical regression model suggested that M18L loss was correlated with a higher likelihood of developing dementia.…”
Section: Gaba System Changes In Alzheimer’s Disease (Ad)mentioning
confidence: 99%
“…However, other neuropathological processes are likely to contribute to the dysfunctional E/I network balance in the hippocampus that leads to cognitive deterioration. Although cognitive decline in AD has been largely related to Aβ oligomers and the glutamatergic system through multiple interactions [31,32], there is growing evidence to suggest that cognitive decline in the AD brain is influenced and also partly precipitated by altered GABAergic function [19], and this has been linked to cognitive decline [33]. In the extrasynaptic space, Aβ 1-42 mediates increase in ambient GABA levels which chronically activates tonic inhibitory currents in the hippocampus, that are involved in the maintenance of the excitatory network and synchronization, and in turn might contribute to the cognitive deficits -but the exact mechanism requires further elucidation.…”
Section: Resultsmentioning
confidence: 99%